Educational Value of Omar and Hana Film for Early Children In The Perspective of Humanistic Theory - Norhidayah, Siti; Surawan, Surawan; Hasanah, Sayyidatul (Proceeding International Conference on Religion, Science and Education, 2025)
Early childhood is at an important developmental phase that requires educational media that supports character building and moral values. The movie “Omar and Hana” is one of the movies that can be used as an educational media that can entertain as well as educate. In addition, the animated film “Omar and Hana” also presents moral values and religious education that can be watched by children. This study aims to analyze the educational values contained in the film from the perspective of humanistic theory which emphasizes the optimal development of individual potential, self-understanding, and self-actualization. This research uses a library research method with a qualitative approach through primary data sources and secondary data sources. Data collection techniques are carried out through observation, namely direct observation and through documentation techniques by collecting and including documents, both in the form of images and works of a person. Data analysis in this research uses Roland Barthes’ semiotic method, which focuses on analyzing the meaning system of denotation, connotation, and myth. The results of this study illustrate that the animated film “Omar and Hana” contains values that are in accordance with the principles of humanistic theory. So, it can be concluded that this film acts as a learning media that can support the moral and emotional development of early childhood, as well as instill the teachings of Islam in a fun and easy-to-understand way for children.